Analysis of the current situation and risk factors of nosocomial infections in oral cancer patients after surgery - Aimin Zhang; Lurui Yu; Xiaoli Wang; Xiaofang Huang; Tao Zhang; Xianghao Kong; Xiaohui Chi (World Journal of Surgical Oncology)
Abstract Background To investigate the current situation of nosocomial infections in oral cancer patients after surgery, explore possible risk factors for nosocomial infections, screen high-risk populations for nosocomial infections after oral cancer surgery in the early stage, and provide scientific basis for the prevention and control of nosocomial infections in oral cancer patients after surgery. Methods 201 patients with oral cancer who underwent surgery in the Department of Oral and Maxillofacial Surgery of our hospital from January 2019 to December 2023 were collected, and their clinical data were observed. Statistics on the incidence of nosocomial infections, infection sites, and pathogenic bacteria in patients undergoing oral cancer surgery. Through univariate analysis and multivariate logistic regression analysis, identify the risk factors for nosocomial infections in oral cancer patients after surgery. Results This study included 201 patients undergoing oral cancer surgery, with 24 cases of nosocomial infections and a nosocomial infection rate of 11.91%. Surgical incision infection is the most common site of infection, accounting for 45.83%, followed by pulmonary infection, accounting for 33.33%. Through pathogen examination, a total of 22 strains of pathogens were found, including 14 Gram negative bacteria (63.64%) and 7 Gram positive bacteria (31.82%). The univariate analysis found that 11 items included: smoking history, drinking history, diabetes, operation duration, skin flap repair, intraoperative bleeding, preventive use of antibiotics, tracheal intubation, gastric tube retention time, venous thromboembolism on the operation day, preoperative oral scaling, which may be the risk factors for nosocomial infection after oral cancer surgery. Logistic regression analysis showed that six independent risk factors of nosocomial infection after oral cancer surgery included: diabetes, skin flap repair, intraoperative bleeding, tracheal intubation, gastric tube retention time, and venous thromboembolism on the day of operation. Conclusion Oral cancer surgery patients are at high risk of infection, and targeted monitoring of oral cancer surgery patients should be strengthened. Preventive measures should be taken for risk factors to reduce nosocomial infection rates.